Identifying the frequency of mismatch repair deficiency in endometrial carcinoma in a tertiary care hospital - Khatoon, Farhana; Begum, Shirin Akter; Dey, Bishnu Pada; Islam, Jannatul; Akter, Naznine; Nihar, Fatema; Ara, Rowson; Alam, Babrul (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Mismatch repair deficiency (MMRd) is a pivotal genetic defect that significantly contributes to the pathogenesis of various cancers, particularly colorectal and endometrial cancers. The mismatch repair (MMR) system is essential for maintaining genomic stability by correcting base-base mismatches and insertion-deletion loops that occur during DNA replication. The aim of the study was to investigate the frequency and patterns of MMR protein deficiency in endometrial cancer and their association with clinical and pathological characteristics. Methods: This cross-sectional observational study was conducted at the Department of Gynecological Oncology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, from March 2022 to February 2023. The study included all patients admitted with histologically confirmed endometrial carcinoma, diagnosed via endometrial fractional curettage or diagnostic D&C, who were admitted for surgical management. Results: In this study of endometrial cancer, 49 participants were analyzed for mismatch repair (MMR) protein status. MMR deficiency (MMRd) was observed in 16 cases (32.7%). Among 16 MMR deficient EC, isolated single protein loss was in 5 (31.25%) and multiple loss was in 11(68.75%) cases. Family history of malignancy often correlated with MSH2 loss. MMRd was significantly associated with higher cancer stages. Immunohistochemistry proved effective for identifying MMR status, facilitating Lynch syndrome screening and subsequent clinical management. These findings underscore the importance of MMR testing in endometrial cancer for prognosis and treatment decisions. Conclusions: This study underscores the importance of mismatch repair (MMR) protein status in the prognosis of endometrial cancer (EC).